ANALISIS OPTIMASI KOMBINASI CABANG USAHATANI SAYURAN DI DESA TAWANGARGO, KECAMATAN KARANGPLOSO, KABUPATEN MALANG - Auliyac Infi Khusnul Khotimah (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
AbstractThe purpose of this research is to determine optimization of vegetables’ farming pattern combinations and give a recommendation to the farmers in order to increase the revenue. This research is determined with purposive sampling in Tawangargo Village, Karangploso District, Malang Regency. The analysis method of this research is using linear programming analysis with simplex method. The results show that the farming pattern combination which gives the most maximum revenue is combination model 1 consists of tomato, mustar green, and cayenne pepper. The maximum revenue value is Rp 17.049.364,00. The optimum production of tomato (????1) is 8.530 kg, mustard green (????2) is 3.230 kg, and cayenne pepper (????3) is 2.197 kg.Keyword : farming pattern combinations, Tawangargo Village, optimization.